2018
DOI: 10.1161/jaha.118.010025
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Therapy Improves Cardiac Function in a Model of Chronic Ischemic Heart Failure: Evidence for a Mechanism Involving VEGF Signaling and the Extracellular Matrix

Abstract: Background Mechanical stimulation of acute ischemic myocardium by shock wave therapy ( SWT ) is known to improve cardiac function by induction of angiogenesis. However, SWT in chronic heart failure is poorly understood. We aimed to study whether mechanical stimulation upon SWT improves heart function in chronic ischemic heart failure by induction of angiogenesis and postnatal vasculogenesis and to dissect underlying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 44 publications
5
33
1
2
Order By: Relevance
“…Most of these effects could not be mimicked by poly(I:C) exposure but were strictly dependent on TLR3. Both TLR3 stimulation as well as SWT have been described to induce release of growth factors, including VEGF, FGF, and NGF (10,21). Consistently, we observed upregulation of VEGF and its receptor VEGFR2 (Supplemental Figure 2).…”
Section: Figure 2 Swt Reduces Spinal Cord Damage and Neuronal Degenesupporting
confidence: 86%
See 2 more Smart Citations
“…Most of these effects could not be mimicked by poly(I:C) exposure but were strictly dependent on TLR3. Both TLR3 stimulation as well as SWT have been described to induce release of growth factors, including VEGF, FGF, and NGF (10,21). Consistently, we observed upregulation of VEGF and its receptor VEGFR2 (Supplemental Figure 2).…”
Section: Figure 2 Swt Reduces Spinal Cord Damage and Neuronal Degenesupporting
confidence: 86%
“…Previously, our group showed that SWT reduces scarring after myocardial infarction (10). To analyze whether SWT may decrease lesion size after SCI, we performed MRI of the spinal cord ( Figure 1D).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…ESWTs have been applied as a successful therapy in heart failure and cardiovascular diseases in humans 43 – 45 . Moreover, in vivo experiments carried out in rats in the presence of LPS or ESWTs resulted in post-infarct cardiac tissue regeneration 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Since then, multiple groups have replicated these results, although mostly with an invasive methodology that applies the SWT directly to the affected myocardial area. This invasive protocol has been tested in mice [ 81 ], rats [ 82 ], and finally in pigs [ 83 ], with very similar outcomes in the treatment group as observed by Nishida et al The therapeutic effect seems to be driven mainly by increased angiogenesis via the upregulation of VEGF and chemoattraction of endothelial cells via stromal cell-derived factor 1 [ 81 ].…”
Section: Cell-free Cardiac Regeneration Therapiesmentioning
confidence: 96%